Meningkatkan Kemampuan Membaca Fasih Al-Qur'an Melalui Video Pembelajaran Interaktif Pada Mata Pelajaran Al-Qur'an Hadist di MTS Islamiyah - Khairul Umam; Kamelyna Emma (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This study aims to improve students' ability to read the Qur'an fluently through interactive learning videos in the subject of Al-Qur'an Hadith at MTs Islamiyah. The method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection. The research subjects were 30 eighth-grade students. Data were collected through reading ability tests, observations, and interviews, then analyzed descriptively. The results showed a significant improvement in the ability to read the Qur'an fluently. In the pre-cycle, students' learning mastery only reached 50% with an average score of 65. After the implementation of interactive learning videos, mastery increased to 70% with an average score of 75 in the first cycle and 90% with an average score of 85 in the second cycle. This improvement was also seen in students' interest and active participation during the learning process. In conclusion, the use of interactive learning videos is effective in enhancing the ability to read the Qur'an fluently. It is recommended that teachers continue to integrate interactive learning media to improve the quality of learning, especially in the Al-Qur'an Hadith subject.